Why intervention in Afghan media failed to provide support for peace talks - Lynch, Jake; Freear, Matt (Frontiers in Communication, 2023)
This article presents and discusses data from two research methods on journalism in Afghanistan before the Taliban takeover of power in August 2021. News reports from the time of the intra-Afghan peace talks in September 2020 were analysed using the Peace Journalism model. These were found to be predominantly War Journalism, leaving audiences cognitively primed for violent conflict responses and likely to overlook or fail to value peace initiatives. Interviews with 16 Afghan journalists revealed this pattern to be at odds with their aspirations and role perceptions. They wanted to report more in the style of Peace Journalism: revealing backgrounds and contexts; highlighting successes and achievements; giving a voice to all rival parties, and covering peace initiatives from whatever level. The constraints they identified, as impeding their preferred reporting approaches, were categorised using Reese and Shoemaker’s Hierarchy of Influences model. Some were attributed to the commercial competitive market structure of Afghan media under the internationally supported government, after an initial infusion of development aid was reduced. In any such intervention in future, it is argued, news can play a positive role in building a constituency for peace – but only if aid interventions ensure that media are not left to operate on a purely commercial basis.